APLIKASI TUNTUNAN SHALAT LENGKAP (APPS-TUSHOLE) BERBASIS MOBILE ANDROID (STUDI KASUS DI MAJELIS ULAMA INDONESIA (MUI) JAMBI) - TRAH, EFITRA FITRAH (FORTECH (Journal of Information Technology), 2020)
Prayer is a primary obligation for Muslims towards Allah SWT. Imagine that Prayer is the pillar of religion and the deeds of a servant who will first be accounted for in the Mahsyar. In worship, prayer must be orderly and in accordance with the procedures that have been determined. At present learning prayer is not a complicated thing to learn either by using media books and information technology media. Complete Mobile Guidance Application based on Android Mobile at the Indonesian Ulema Council (MUI) Jambi Province was designed using android information technology that has features about prayer. Of course with this prayer application Android smartphone users can take advantage of free time to learn prayer effectively and flexibly wherever and whenever they are.